2018
DOI: 10.3892/ol.2018.9840
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of melanoma cell adhesion molecule CD146 and VEGFA expression in epithelial ovarian cancer

Abstract: Ovarian cancer is the fifth most common type of cancer in females; however, its asymptomatic progression and the lack of an efficient screening strategy leads to late diagnosis. The present study aimed to investigate the expression levels of cluster of differentiation (CD)146 and vascular endothelial growth factor A (VEGFA) in epithelial ovarian cancer, and their clinical significance. A total of 52 ovarian samples were tested, of which 22 were from patients with epithelial ovarian cancer and 30 were from non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Subsequently, Jiang's report indicates CD146 promotes the migration of ECs and the formation of microvasculature by enhancing VEGFR2 phosphorylation and downstream signaling (AKT/p38 MAPKs/NF-κB) activation (Jiang et al, 2012). Interestingly, Zhou's research indicated that the gene and protein levels of CD146 and VEGFRA were increased in patients with EOC compared to those of non-cancer patients (Zhou et al, 2019).…”
Section: Endothelial Cellsmentioning
confidence: 99%
“…Subsequently, Jiang's report indicates CD146 promotes the migration of ECs and the formation of microvasculature by enhancing VEGFR2 phosphorylation and downstream signaling (AKT/p38 MAPKs/NF-κB) activation (Jiang et al, 2012). Interestingly, Zhou's research indicated that the gene and protein levels of CD146 and VEGFRA were increased in patients with EOC compared to those of non-cancer patients (Zhou et al, 2019).…”
Section: Endothelial Cellsmentioning
confidence: 99%
“…Under pathological conditions, such as inflammation and tumorigenesis, CD146 was upregulated in the related cells and has been identified as a reliable marker for numerous types of cancers. Accumulating evidence shows that CD146 overexpression has been linked to either the initial development of the primary lesion or progression to metastases of most of cancer types, primarily including melanoma, 1 , 27 29 breast, 6 , 30 , 31 ovarian, 32 35 lung, 36 , 37 prostate, 38 40 glioma, 41 kidney, 42 hepatic, 43 , 44 and gastric cancers. 21 , 45 In 2017, Nollet et al reported that TsCD146 mAb (for tumor specific anti-CD146 monoclonal antibody) can specifically recognize CD146 expressed in cancer cells but not CD146 in physiological vessels, suggesting that structural features of cancer CD146 differ from those of physiological CD146.…”
Section: The Expression Profile Of Cd146 Proteinmentioning
confidence: 99%
“…Additionally, high MCAM expression increased disease progression in OvCa patients, suggesting that MCAM modulation by MITF is a clinically important factor that accelerates OvCa progression, by promoting metastasis to the peritoneum, and worsens the prognosis. Therefore, MCAM also have the potential to be a biomarker to predict the prognosis of OvCa ( Figure 5 I) [ 48 ]. Collectively, the MITF/MCAM axis may significantly contribute to migration, invasion, and tumorigenicity in vivo, but research studies have not yet explored this question.…”
Section: Discussionmentioning
confidence: 99%